Fluorescence spectroscopy - Brand, Ludwig; Johnson, Michael L., 1947- (Methods in enzymology, 1997)
The critically acclaimed laboratory standard for more than forty years, Methods in Enzymology is one of the most highly respected publications in the field of biochemistry. Since 1955, each volume has been eagerly awaited, frequently consulted, and praised by researchers and reviewers alike. More than 270 volumes have been published (all of them still in print) and much of the material is relevant even today--truly an essential publication for researchers in all fields of life sciences. Key Features * Fluorescence in biophysics * Fluorescence as a tool for studying proteins * Determination of ground-state dissociation constant by fluorescence spectroscopy * Fluorescence spectroscopy of protein-protein and protein-nucleic acid interactions * Fluorescence methods for studying equilibrium macromolecule-liquid interactions * Methods for detecting molecular clusters on cell surfaces.